Effects of M-DEPTH model of depression care on maternal depression, functioning, and HIV care adherence, and infant developmental over eighteen months post-partum: results from a cluster randomized controlled trial - Glenn J. Wagner; Bonnie Ghosh-Dastidar; Violet Gwokyalya; Laura J. Faherty; Jolly Beyeza-Kashesya; Juliet Nakku; Linda Kisaakye Nabitaka; Dickens Akena; Janet Nakigudde; Victoria Ngo; Ryan McBain; Hafsa Lukwata; et al. (BMC Pregnancy and Childbirth)
Abstract Background Perinatal depression is associated with poor outcomes related to HIV care adherence, maternal functioning, and early child development. We examined whether the M-DEPTH (Maternal Depression Treatment in HIV) depression care model—including antidepressant therapy and individual problem-solving therapy—and depression alleviation would affect improvement in each of these outcome domains. Methods A sample of 354 pregnant women living with HIV (WLH) with at least mild depressive symptoms (177 in each of intervention and usual care control arms) enrolled in a cluster randomized controlled trial across eight antenatal care clinics in Uganda and had a live birth delivery. Longitudinal mixed effects models were used to examine survey data and chart-abstracted HIV viral load and antiretroviral pharmacy refill data collected at baseline and months 2, 6, 12 and 18 post-partum. Results 69% had clinical depression at enrollment; 70% of women in the intervention group (including 96% of those with clinical depression) received depression treatment. Mixed-effects longitudinal regression analysis showed (1) strong effects of the intervention on maternal depression at each post-partum follow-up assessment; and (2) moderate effects of the intervention and reduced depression on maternal functioning (self-care and infant care, in particular). However, there was little evidence of effects of the intervention and depression reduction on early child development, maternal viral suppression, or ART adherence. Conclusion These findings suggest that depression care for pregnant WLH is important for maternal mental health, but it also helps women to better manage parenting and care for their infant. Supplementary interventions may be needed to impact early child development. Trial registration The trial was registered with the NIH Clinical Trial Registry (clinicaltrials.gov: NCT03892915) on 27/03/2019.